The Urgency of Formulation of Responsive Criminal Law Policies to the Values of the Madura Carok Tradition in the Framework of Restorative Justice and Legal Pluralism in Indonesia - Arafah, Reny; Anggoro, Purwadi Wahyu; Setiono, Joko (Greenation Publisher & Yayasan Global Resarch National, 2025)
The tradition of carok in Madurese society is a practice of conflict resolution that is deeply rooted in the values of honor and self-respect. Although socio-culturally carok is understood as a form of defending one's dignity, this practice contradicts the national criminal justice system, which prioritizes the principles of legality and protection of the right to life. This disparity creates challenges in law enforcement, as the state often fails to accommodate local values in the formulation of criminal policies. This study aims to analyze the urgency of formulating criminal policies that are responsive to the values of the carok tradition, using restorative justice and legal pluralism as integrative solutions. The method used is normative jurisprudence with a legislative approach and the theories of legal pluralism and restorative justice. The analysis shows that the new Criminal Code (Law No. 1 of 2023) through Article 2 has recognized the existence of customary law, but it has not yet fully addressed sociocultural challenges such as carok. A reformulation of criminal policy is needed that not only emphasizes repressive aspects but also accommodates community-based resolutions through penal mediation and the role of customary leaders. With this approach, it is expected that reconciliation between state legal values and local wisdom will occur to create substantive justice rooted in the social reality of the community.